2014
DOI: 10.1111/dar.12207
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of medical marijuana use in California, 2012

Abstract: Our study's results lend support to the idea that medical marijuana is used equally by many groups of people and is not exclusively used by any one specific group. As more states approve marijuana use for medical purposes, it is important to track medical marijuana use as a health-related behaviour and risk factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
59
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 25 publications
(42 reference statements)
1
59
0
4
Order By: Relevance
“…In the Ware et al cohort, 35% of patients had previously used cannabis, and of those, 15% used it specifically for pain relief. Those data are corroborated by data from the California Behavior Risk Factor Surveillance System, which showed that 5% of telephone respondents reported medical marijuana use and that respondents who used tended to be younger and to have conditions such as chronic pain 7 . A survey of a mixed cohort of patients from the United Kingdom reported on the opinions of 2969 respondents about cannabis use between 1998 and 2002 9 .…”
Section: Discussionmentioning
confidence: 65%
“…In the Ware et al cohort, 35% of patients had previously used cannabis, and of those, 15% used it specifically for pain relief. Those data are corroborated by data from the California Behavior Risk Factor Surveillance System, which showed that 5% of telephone respondents reported medical marijuana use and that respondents who used tended to be younger and to have conditions such as chronic pain 7 . A survey of a mixed cohort of patients from the United Kingdom reported on the opinions of 2969 respondents about cannabis use between 1998 and 2002 9 .…”
Section: Discussionmentioning
confidence: 65%
“…To learn more about the use of medical marijuana, a question was added to the California version of the Behavioral Risk Factor Surveillance System telephone survey in 2012 and the results showed the prevalence of ever having used medical marijuana was highest among white adults and younger adults ages 18–24 (Ryan-Ibarra et al, 2015). …”
Section: Resultsmentioning
confidence: 99%
“…Considering the fact that illicit market purchase behaviors differ by demographics, medical marijuana purchase behaviors might differ by patient demographic characteristics as well. In fact, trends of medical marijuana patients in California from 2001 to 2012 parallel high-quantity purchasers identified in illicit markets, both being predominantly men, young adults, and non-Hispanic Whites (O’Connell & Bou-Matar 2007; Ryan-Ibarra, Induni & Ewing 2014). …”
mentioning
confidence: 99%
“…Patients have primarily reported medical conditions of chronic pain, sleeping problems, and anxiety (O’Connell & Bou-Matar 2007; Ryan-Ibarra et al 2014). Among these patients, it is possible that including chronic pain as a qualifying condition for marijuana could have variable influences on effects of medical marijuana recommendation and distribution policies (Pacula et al 2015).…”
mentioning
confidence: 99%